Rapid Resolution of Anabolic Androgenic Steroid‐Induced Refractory Pruritus and Bile Cast Nephropathy With Therapeutic Plasma Exchange - Samuel Wong; Danny Con; Avik Majumdar (JGH Open)
ABSTRACT The proportion of non‐paracetamol drug‐induced liver injury (DILI) is increasing in Australia and other Western countries. Androgenic anabolic steroids (AAS) commonly cause a bland cholestasis that can persist for months despite withdrawal. A 35‐year‐old male presented with progressive painless jaundice associated with pruritus, nausea, loss of weight, dark urine, and pale stools. He had recently commenced AAS; DILI was suspected and confirmed on biopsy. His pruritus was refractory to medical therapy, and PLEX was commenced. He also developed renal failure from bile cast nephropathy (BCN) and required hemodialysis. At 10 weeks post‐discharge, his pruritus and jaundice were significantly improved, and his renal function had completely recovered. The case adds to the growing evidence that PLEX can be used safely and effectively to treat cholestatic pruritus and BCN.